Implementasi Sistem Rekomendasi Restoran Untuk Peningkatan Pengalaman Pengguna Menggunakan Metode Analytical Hierarchy Process (AHP) Berbasis Website Di Kota Depok - Raihan Akmal Yusuf; Jaka Sutresna (Jurnal Ticom: Technology of Information and Communication, 2026)
The large number of restaurant options in Depok City creates difficulties for users in selecting restaurants that match their personal preferences. This issue is further caused by the lack of a web-based recommendation system capable of systematically processing multiple selection criteria. This study aims to design and implement a web-based restaurant recommendation system using the Analytical Hierarchy Process (AHP) method and to analyze its application in determining criteria weights and restaurant recommendations. The AHP method is applied to evaluate price, distance, food quality, service, and atmosphere based on user preferences through pairwise comparisons. The system is developed using PHP and MySQL. System testing is conducted using black box testing, white box testing, and user response evaluation through questionnaires. The results indicate that the proposed system is able to generate objective and preference-based restaurant recommendations and effectively improve user experience in selecting restaurants in Depok City.